Consequent of the Human Resources Development and Job Satisfaction: Empirical Study on PT Bank BNI Medan - Sembiring, Hendri; Ferine, Kiki Farida (International Review of Management and Marketing, 2018)
This research aimed to present about analysis influence of human resource development and job satisfaction toward performance employee's of PT Bank BNI Terrain. The research type is quantitative descriptive using the method. Resources of the data which used in this research involving primary and secondary data. The result of this research shows that human resource development has significant influence toward employee's performance, job satisfaction has significant influence toward employee's performance, and together human resource development and job satisfaction has significant influence toward employee's performance of PT. Bank BNI. Hopefully this research could add and enrich research about influence of human resource development and job satisfaction toward employees performance. Keywords: human resource development, job satisfaction, employees performance. JEL Classifications: J28, O15